Rest in pieces: an interpretive model of early medieval ‘grave robbery’ - van Haperen, Martine C. (Medieval and Modern Matters, 2010)
Abstract Many early medieval cemeteries contain graves that were reopened in the years following the burials. In the traditional literature, such post-depositional interventions are usually interpreted as cases of grave robbery, a criminal activity primarily instigated by economic motives. However, as has been noted by various scholars, not all aspects of these practices tally with this hypothesis equally well. The ‘robbers’ often left a number of artefacts behind, removed some of the deceased’s bones and then refilled the grave. These practices therefore seem to have originated from a motivation more complex than a simple desire to obtain the grave goods. The current article contains a re-evaluation of the main technical and theoretical aspects of the debate. Working from an ethnographically informed perspective, the author proposes an alternative model for the interpretation of grave reopenings, emphasizing the opportunities that these events offered for the interaction between the living and the dead. Artefacts and bones from reopened graves may have served as ‘relics’, enabling the ancestors to be physically present among their living descendants. It is therefore suggested that grave reopenings should not be considered deviant behaviour, but be studied as part of the general sequence of practices that were performed following a death. Abstract La plupart des cimetières du haut Moyen Âge révèlent des sépultures qui ont ont été réouvertes dans les années qui suivent l’enterrement. Dans la littérature, de telles interventions post-dépositionnelles sont traditionnellement interprétées comme des indices de pillage, action criminelle motivée par des intérêts pécuniaires. Néanmoins, comme souligné par plusieurs auteurs, tous les aspects de ces pratiques ne confortent pas l’hypothèse de la violation de sépulture. Les pilleurs laissent souvent un certain nombre d’objets sur place, déplacent certains ossements et remblaient la fosse. Ces pratiques semblent donc naître de plus complexes motivations que le simple attrait des mobiliers funéraires. Cet article réévalue les aspects du débat à la fois sur les plans technique et théorique. L’auteur adopte une perspective ethnographique pour proposer un modèle alternatif d’interprétation des réouvertures de tombes, attirant l’attention sur les opportunités que ces actions offrent en termes d’interaction entre les sphères du vivant et de la mort. Les objets et les ossements issus de sépultures réouvertes ont par exemple pu servir de “reliques”, rendant l’ancêtre physiquement présent parmi ses descendants. L’auteur suggère aussi que ces pratiques ne devraient pas uniquement être considérées comme exclusivement marginales et condamnables, mais comme participant de l’ensemble des pratiques suivant la mort.